Sistem Pakar Diagnosa Stress Pada Mahasiswa Tingkat Akhir Dengan Menggunakan Metode Certainty Factor Berbasis Android (Studi Kasus: Mahasiswa Tingkat Akhir STMIK Bandung) - Indra Maulana Yusup Kusumah; Linda Apriyanti; Puti Rahina Rafki (LPPM STMIK Bandung, 2022)
Expert System for Diagnosing Stress in Final Year Students using the Certainty Factor Method is an android-based application that can measure the level of stress experienced by final year students. Stress is one of the things that can cause obstacles in the completion of thesis in final year students. By creating this application, it is expected to help students in measuring the level of stress experienced and can immediately overcome it. The application is made using the Kotlin programming language, Android Studio IDE, and Firebase Firestore as a Database.